PENINGKATAN KEMAMPUAN BERBAHASA ANAK USIA 5-6 TAHUN MELALUI PERMAINAN MEDIA KARTU HURUF BERGAMBAR DI TK PELANGI TENGGARONG SEBERANG TAHUN PEMBELAJARAN 2016-2017 - Tatik - Rahayu; Mahkamah - Brantasari (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2019)
This study aims to find out how to improve the language skills of children aged 5-6 years through playing illustrated letter card media at Pelangi Tenggarong Seberang Kindergarten in the 2016/2017 learning year. This type of research uses the class action research method (CAR) carried out in two cycles. The object of this research is 20 children. Research data collection uses observation sheets while the results are analyzed using quantitative descriptive methods. The results of data analysis showed that there was an increase in pre-cycle to the first cycle of 35%. In the second cycle increased 91.11%. The conclusion in this study, that the use of pictorial letter card media can improve language skills in children aged 5-6 years in Pelangi Kindergarten.